Determinan Stunting pada Balita di Masa Pandemi Covid-19 di Wilayah Kerja Puskesmas Pirak Timu Kabupaten Aceh Utara - Tampubolon, Elmina; Girsang, Vierto Irennius (Jurnal Kesehatan Komunitas, 2023)
The Covid-19 pandemic in Indonesia has prevented several basic health services, especially Posyandu, from being carried out, which can hinder the achievement of the 2024 national target, which is to reduce the stunting rate to 14%. The aim of the study was to analyze the determinants of stunting in toddlers during the Covid-19 pandemic in the Pirak Timu Community Health Center, North Aceh District. This type of research is quantitative analytic. The sample of this study was stunted toddler mothers who lived in the working area of the Pirak Timu Health Center, North Aceh Regency, totaling 65 people. Data collection was carried out using the interview method using a questionnaire carried out from December 2021 to January 1st, 2022. Data analysis was univariate, bivariate, and multivariate using a multiple logistic regression test. Variables related to the incidence of stunting in toddlers are history of exclusive breastfeeding, diet, knowledge, and income. Meanwhile, the variable that is not related to the incidence of stunting is parity. The conclusion obtained is that there is a relationship between a history of exclusive breastfeeding, diet, knowledge, and income with the incidence of stunting in toddlers during the Covid-19 pandemic at the Pirak Timu Health Center, North Aceh District